Iron plays a key role in the cytodifferentiation of human periodontal ligament cells. (28th May 2013) - Hou, J.; Yamada, S.; Kajikawa, T.; Ozaki, N.; Awata, T.; Yamaba, S.; Fujihara, C.; Murakami, S.
<x xml:space="preserve">Abstract</x> Background and Objective The periodontal ligament (PDL) is vital to maintaining the homeostasis of the tooth and periodontal tissue. The influence of iron levels on the cytodifferentiation of PDL cells has not been studied, despite evidence that iron overload or deficiency can have adverse effects on alveolar bone density. The purpose of this study was to examine the effects of altered iron levels on cytodifferentiation in human PDL cells. Material and Methods Human PDL cells were incubated with culture media supplemented with 10–50 μm ammonium ferric citrate or 5 μm deferoxamine (an iron chelator) during differentiation. Intracellular iron status was assessed by measuring changes in the expression of ferritin RNA and protein. PDL cell differentiation and function were evaluated by measuring osteoblast differentiation gene markers and the capacity of cultures to form mineralized nodules. Results Iron accumulation resulted in upregulation of light and heavy chain ferritin proteins. Concurrently, osteoblast differentiation gene markers and mineralized nodule formation were suppressed. Iron deficiency resulted in downregulation of light and heavy chain ferritin proteins, suppression of alkaline phosphatase activity and formation of mineralized nodules during PDL cell differentiation. Conclusion We conclude that iron is critical for normal cell differentiation of human PDL cells.